Economic Incentives for the Modernization of the Electricity Distribution System Operators' Network Infrastructure - Serebrennikov В.S.; Petrova K.H.; Serebrennikov S.V.; Savelenko I.V. (Problems of the Regional Energetics)
The paper aimed at improving an economic mechanism for incentivizing distribution system operators to retrofit electricity networks and provide better services. The suggested approach envisages setting up operators' profitability relating to their rating scores, which were calculated considering essential criteria, in particular technical level of networks, efficiency, congestion, reliability, innovativeness, and quality of electricity. For this purpose, operators were ranked by the rating scores that allowed to elaborate methodology for distribution tariffs calculation individually. The essential findings: comprehensive assessment and ranking were based on an analysis of 20 key performance indicators of the networks' technical level; application of additive convolution considering the significance of indicators by Fishburn's weighting approach ensured their proper aggregation; using the principles of fuzzy logic, the aggregated values for the technical level of network infrastructure were calculated. The minimum tariff rates were computed for each operator according to the break-even point, with the maximum tariff rate being equal for the whole sample. A linear functional transformation provided a transition from the aggregated scores to specific tariff rates. Consequently, the best-rated operators received the maximum tariff rate, and the less-rated operators received relevantly lower rates. By varying the slope of the suggested tariff function, one can adjust the dynamics of the tariff rate change. The assessment of 24 operators allowed to verify the elaborated methodology for distribution tariff setting. The application of unbiased rating assessment by a set of designed sector-specific indicators allowed setting up adequate and efficient tariff rates aimed at incentivizing network upgrades.